Seleção precoce de clones de batata adaptados às condições temperada e subtropical de cultivo do sul do Brasil - Bandinelli, Maurício Guerra (2014)
Experiments were conducted in order to (i) evaluate the use of canonical correlation to identify plant and tuber traits that can be used for early identification of superior potato clones and (ii) develop and validate a method of early selection of potato clones for tuber dormancy, to identify clones with short or long dormancy, with the purpose of being used respectively in subtropical and temperate growing conditions. The study of canonical correlation analysis was conducted in two generations (seedling and tuber) with nine families and a total of 358 clones. The seedling generation (G1) was conducted in a greenhouse in the winter of 2008, and the tuber generation (G2) on the field during the fall season of 2009. From both generations 13 plant and tuber traits were evaluated: height of the main stem (HMS), fresh weight of shoots (FWS), fresh weight of stolons (FWS), fresh weight of tubers (FWT), number of tubers per plant (NTP), elongated-shaped tuber (EST), flattened-shaped tuber (FST), skin texture (SKT), pointed ends (POI), secondary growth (SEG), eye depth (DEP), days to break dormancy (DBD) and number of sprouts per tuber (NST). The variability among families was significant for all traits in both generations except for POI in the first generation and FWS, SEG and DEP in the second generation. The linear correlations between G1 and G2 were significant, positive and high for 12 out of 13 traits evaluated. The canonical correlation analysis showed that there is an association between plant and tuber traits in the two generations. However, no general rule was observed for the early selection of clones, valid for any family, being the evaluation of clones in the set more efficient to identify the correlation of characters between the generations. In order to develop and validate a method of early selection of clones for tuber dormancy, experiments were conducted between the years of 2010 and 2013, beginning with two independent sets of clones. In 2010, seedling generation of the first set (19 clonal families) was conducted in a greenhouse. Tubers from each genotype were harvested (total of 1,145 clones or minitubers), which were treated with 30 mg L-1 gibberellic acid and stored at 20 °C for breaking dormancy. After 45 days of storage four groups of clones were formed according to the number of days (45, 60, 75 and 90 days) required for breaking dormancy. A random sample of tubers of each group was used for the summer field cultivation. At harvest, four tubers were separated from each clone to assess dormancy and apical dominance under storage of 20 °C. In 2012, a second set with 1,269 clones (minitubers of 16 families) was produced in order to separate five groups of clones according to the number of days (30, 45, 60, 75 and 90 days) required for breaking dormancy of tubers. For both sets of clones, a completely randomized design with four replicates of each clone was utilized. There was a pattern of dormancy breaking and direct relationship within the dormancy period of the tubers between the two generations, that made possible to develop and validate an early selection method. This method enables the assembly of clones with similar dormancy level as of the seedling generation, i.e., allows early identification of clones with short or long dormancy, with potential as new adapted cultivars respectively for subtropical and temperate growing conditions of southern Brazil.